Halal Perception, Product Quality, and Customer Satisfaction as Determinants of Repurchase Intention in Halal Coffee Beverages - Eka Tamia Mahakami; Yolanda Masnita; Kurniawati Kurniawati (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This research aims to examine the influence of health awareness, previous product quality experience, halal literacy, and risk perception on attitudes that drive repurchase intentions toward halal coffee beverages. This research specifically focuses on halal coffee beverages sold in franchised coffee outlets that have obtained halal certification from the Indonesian Ulema Council (MUI). The sampling method used in this research was non-probability sampling. Questionnaires were administered to a sample of respondents using the KoboToolbox application. The data processing method used AMOS SEM. The results of this research indicate that health awareness and perceived risk have no positive or significant impact on repurchase intention mediated by attitude. Past product quality experience and halal literacy have a positive and significant impact on repurchase intention mediated by attitude. Attitude has a positive and significant impact on repurchase intention. The results are expected to contribute to the government and franchise businesses in encouraging increased consumer repurchase intentions for halal coffee beverages.